Quantitative Psychology Research The 79th Annual Meeting of the Psychometric Society, Madison, Wisconsin, 2014 - van der Ark, L. Andries; Bolt, Daniel M.; Wang, Wen-Chung; Douglas, Jeffrey A.; Chow, Sy-Miin (Springer Proceedings in Mathematics & Statistics, 2015)
These research articles from the 79th Annual Meeting of the Psychometric Society (IMPS) cover timely quantitative psychology topics, including new methods in item response theory, computerized adaptive testing, cognitive diagnostic modeling, and psychological scaling. Topics within general quantitative methodology include structural equation modeling, factor analysis, causal modeling, mediation, missing data methods, and longitudinal data analysis. These methods will appeal, in particular, to researchers in the social sciences. The 79th annual meeting took place in Madison, WI between July 21nd and 25th, 2014. Previous volumes to showcase work from the Psychometric Society's Meeting are New Developments in Quantitative Psychology: Presentations from the 77th Annual Psychometric Society Meeting (Springer, 2013) and Quantitative Psychology Research: The 78th Annual Meeting of the Psychometric Society  (Springer, 2015).